Differentiated Mechanisms of Biochar Mitigating Straw-Induced Greenhouse Gas Emissions in Two Contrasting Paddy Soils - Wang, Ya-Qi; Bai, Ren; Di, Hong J.; Mo, Liu-Ying; Han, Bing; Zhang, Li-Mei; He, Ji-Zheng (Frontiers in Microbiology, 2018)
Straw returns to the soil is an effective way to improve soil organic carbon and reduce air pollution by straw burning, but this may increase CH4 and N2O emission risks in paddy soils. Biochar has been used as a soil amendment to improve soil fertility and mitigate CH4 and N2O emissions. However, little is known about their interactive effect on CH4 and N2O emissions and the underlying microbial mechanisms. In this study, a two-year pot experiment was conducted on two paddy soil types (an acidic Utisol, TY, and an alkaline Inceptisol, BH) to evaluate the influence of simulated straw and biochar applications on CH4 and N2O emissions, and on related microbial functional genes. Results showed that straw addition markedly increased the cumulative CH4 emissions in both soils by 4.7~9.1 fold and 23.8~72.4 fold at low (S1) and high (S2) straw input rate, respectively, corresponding to a significant increase in mcrA gene abundance. Biochar amendment under the high straw input (BS2) significantly decreased CH4 emissions by more than 50% in both soils, and increased both mcrA gene and pmoA gene abundances, with greater enhance on the pmoA gene and resulting a decreased mcrA/pmoA gene ratio. Moreover, methanotrophs community changed actively in response to straw and biochar amendment in the alkaline BH soil, but remained slightly change in the acidic TY soil. Straw had little effect on N2O emissions at low input rate (S1) but significantly increased N2O emissions at the high input rate (S2). Biochar amendment showed inconsistent effect on N2O emissions, with a decreasing trend in the BH soil but an increasing trend in the TY soil in which high ammonia existed. Correspondingly, increased nirS and nosZ gene abundances and visible community changes in nosZ gene-containing denitrifiers in response to biochar amendment were observed in the BH soil but not in the TY soil. Overall, our results suggested that biochar amendment could markedly mitigate the CH4 and N2O emissions risks under a straw return practice via regulating functional microbes and soil physicochemical properties, while the performance of this practice will vary depending on soil parent material characteristics.